eMagRes (Wiley, 2007)
It includes many articles from the print editions of Encyclopedia of Nuclear Magnetic Resonance and recent EMR Books, as well as new and updated articles published online in eMagRes (formerly the Encyclopedia of Magnetic Resonance)
Gesehen am 21.07.15
Keywords: Datenbank